Admission Rates, Time Trends, Risk Factors, and Outcomes of Ischemic and Hemorrhagic Stroke From German Nationwide Data. (6th December 2022) - Kelly, Dearbhla M.; Feld, Jannik; Rothwell, Peter M.; Reinecke, Holger; Koeppe, Jeanette
Abstract : Background and Objectives: In the past decade, there have been major improvements in the control of risk factors, acute stroke therapies, and rehabilitation after the availability of high-quality evidence and guidelines on best practices in the acute phase. In this changing landscape, we aimed to investigate the stroke admission rates, time trends, risk factors, and outcomes during the period of 2014–2019 using German nationwide data. Methods: We obtained data of all acute stroke hospitalizations by the Federal Statistical Office. All hospitalized cases of adults (age 18 years or older) with acute stroke from the years 2014–2019 were analyzed regarding time trends, risk factors, treatments, morbidity, and in-hospital mortality according to stroke subtype (all-cause/ischemic/hemorrhagic). Results: Between 2014 and 2019, overall stroke hospitalizations in adults (median age = 76 years, [IQR: 65–83 years]) initially increased from 306, 425 in 2014 to peak at 318, 849 in 2017 before falling to again to 312, 692 in 2019, whereas percentage stroke hospitalizations that resulted in death remained stable during this period at 8.5% in 2014 and 8.6% in 2019. In a multivariate model of 1, 882, 930 cases, the strongest predictors of in-hospital stroke mortality were hemorrhagic subtype (adjusted OR [aOR] = 3.06, 95% CI 3.02–3.10; p < 0.001), cancer (aOR = 2.11, 2.06–2.16; p < 0.001), congestive heart failure (aOR = 1.70, 1.67–1.73; p < 0.001), and lower extremity arterial disease (aOR = 1.76, 1.67–1.84; p < 0.001). Discussion: Despite recent advances in acute stroke care over the past decade, the percentage of stroke hospitalizations resulting in death remained unchanged. Further research is needed to determine how best to optimize stroke care pathways for multimorbid patients.